Experimental studies of high-confinement mode plasma response to non-axisymmetric magnetic perturbations in ASDEX Upgrade. (22nd November 2016) - Suttrop, W; Kirk, A; Nazikian, R; Leuthold, N; Strumberger, E; Willensdorfer, M; Cavedon, M; Dunne, M; Fischer, R; Fietz, S; Fuchs, J C; Liu, Y Q; et al.
Abstract: The interaction of externally applied small non-axisymmetric magnetic perturbations (MP) with tokamak high-confinement mode (H-mode) plasmas is reviewed and illustrated by recent experiments in ASDEX Upgrade. The plasma response to the vacuum MP field is amplified by stable ideal kink modes with low toroidal mode number n driven by the H-mode edge pressure gradient (and associated bootstrap current) which is experimentally evidenced by an observable shift of the poloidal mode number m away from field alignment ( m = qn, with q being the safety factor) at the response maximum. A torque scan experiment demonstrates the importance of the perpendicular electron flow for shielding of the resonant magnetic perturbation, as expected from a two-fluid MHD picture. Two significant effects of MP occur in H-mode plasmas at low pedestal collisionality, ν p e d ∗ ⩽ 0.4 : (a) a reduction of the global plasma density by up to 61 % and (b) a reduction of the energy loss associated with edge localised modes (ELMs) by a factor of up to 9. A comprehensive database of ELM mitigation pulses at low ν ∗ in ASDEX Upgrade shows that the degree of ELM mitigation correlates with the reduction of pedestal pressure which in turn is limited and defined by the onset of ELMs, i. e. a modification of the ELM stability limit by the magnetic perturbation.